Sulphur (S) topdressing and organic compost in production, quality and nutrients accumulation of broccoli seeds at planting time - Corrêa, Carla Verônica [UNESP]; Gouveia, Aline Mendes de Sousa [UNESP]; Lanna, Natália de Brito Lima [UNESP]; Martins, Bruno Novaes Menezes [UNESP]; Tavares, Ana Emília Barbosa [UNESP]; Mendonça, Veridiana Zocoler [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP]; Evangelista, Regina Marta [UNESP] (Southern Cross Publishing, 2017)
Most recent studies have focused to the nutrition and fertilizer recommendations of commercial broccoli production. There are a few studies on effect of fertilization on seed production. Although Brazil is a major producer of vegetables, research on seed production of broccoli is scarce. Therefore, it is necessary to develop research lines that increase the information regarding the nutritional requirements for seed production, since in broccoli; there is a 60 days cycle for production, which leads to the understanding of a greater nutritional need of the crop. It is known that sulphur is the second most accumulated nutrient in broccoli seeds. This study aimed to evaluate the effect of doses of sulphur topdressing; and organic compost fertilization on the production and quality of broccoli seeds at planting. The experimental design was a randomized complete block, with ten treatments (5x2 factorial design) and four repetitions. Treatments consisted of five doses of S topdressing (0, 58, 115, 173 and 230 kg S.ha-1) in the presence or absence of organic compost (100 t ha-1) at planting stage. Seed production (mass and number per plant), mass of thousands of seeds, seed quality (germination, first germination count, germination speed index, seedling length, and seedlings fresh weight); and macronutrients accumulation in the seeds were evaluated. The amount of seeds per plant was 9836 and 8005 seeds per plant in the presence or absence of organic compost, respectively. The seeds fresh mass of 45.7 and 33.1 g of seeds per plant was produced with and without organic compost, respectively. However, the other characteristics, such as total germination (G), first count (FC), germination index rate (GIR), and seedling fresh mass (SFM) did not reach any significant differences. Regarding to the doses of sulphur, a linear increase was detected to the equation for all macronutrients extracted in the absence of organic compost at planting. However, in the presence of organic compost (100 t ha-1) at planting, a linear equation was obtained for P, Mg and S. For the other macronutrients, a quadratic function occurred, with average values of 2329.2, 431.4 and 326, 5 mg plant-1 at the maximum doses estimated in 165.56, 146.50 and 171.42 for N, K and Ca, respectively.
Keywords: Brassica oleracea var. italica; Germination; Macronutrients; Mineral nutrition; Vigour